Public procurement as policy instrument for innovation - Dirk Czarnitzki; Paul Hünermund; Nima Moshgbar (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2018)
The use of public procurement to promote private innovation activities has attracted increasing attention recently. Germany implemented a legal change in its procurement framework in 2009, which allowed government agencies to specify innovative aspects of procured products as selection criteria in tender calls. We analyze a representative sample of German firms to investigate whether this reform stimulated innovation in the business sector. Across a wide set of specifications - OLS, nearest-neighbor matching, IV regressions and difference-in-differences - we find a robust and significant effect of innovationdirected public procurement on turnover from new products and services. However, our results show that the effect is largely attributable to innovations of more incremental nature rather than market novelties.
urn:nbn:de:bsz:180-madoc-441780
Keywords: H57; O38; 330; Public Procurement of Innovation; Public Procurement with Contracted Innovation; Technical Change; Research and Development; Econometric Policy Evaluation